Pengaruh Pelayanan Frontliner, Word Of Mouth Dan Kepercayaan Terhadap Loyalitas Nasabah Pada Pt. Bank Perekonomian Rakyat Lengayang Cabang Surantih Pesisir Selatan - Lidya Martha; Suci Aprilia Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of frontliner service, word of mouth, and trust on customer loyalty at Rural Bank (BPR) Lengayang Surantih Branch. This research adopts a quantitative approach. The population consists of 3,326 savings customers based on secondary data from the past year. The sample comprises 97 respondents selected through questionnaire distribution. Data were analyzed using multiple linear regression analysis with a t-test. The results indicate that frontliner service and trust have a significant effect on customer loyalty, whereas word of mouth does not have a significant effect on customer loyalty. These findings suggest that improved service quality and higher levels of customer trust contribute to increased customer loyalty.